Perampanel and decanoic acid show synergistic action against AMPA receptors and seizures. (15th October 2018) - Augustin, Katrin; Williams, Sophie; Cunningham, Mark; Devlin, Anita M.; Friedrich, Maximilian; Jayasekera, Ashan; Hussain, Mohammed A.; Holliman, Damian; Mitchell, Patrick; Jenkins, Alistair; Chen, Philip E.; Walker, Matthew C.; et al.
Summary: Perampanel is an adjunctive treatment for epilepsy that works through the direct inhibition of AMPA receptors. The same molecular mechanism has recently been shown for a fatty acid, decanoic acid, prescribed in the medium chain triglyceride ketogenic diet for the treatment of patients with drug‐resistant epilepsy. Because each compound has been proposed to act through a distinct AMPA receptor binding site, we predicted that perampanel and decanoic acid would act synergistically against AMPA receptors and, consequently, seizures. Here, we show a synergistic interaction between perampanel and decanoic acid in direct AMPA receptor inhibition, in an ex vivo model of seizure activity, and against seizure‐induced activity in human brain slices. These data support a potential role for combination treatment using perampanel and dietary decanoic acid to provide enhanced seizure control.